Dermoscopic features in children with vitiligo and other hypopigmentation disorders - Yu, Shijuan; He, Jingyi; Wang, Hua (Frontiers in Pediatrics, 2025)
ObjectiveTo analyze the application value of dermoscopy in the identification and staging evaluation of vitiligo in children.MethodsWe have analyzed the differences in dermoscopy between vitiligo and other hypopigmentation disorders. Meanwhile, the dermatoscopic differences between active and stable vitiligo were also compared. At the same time, the results of diagnosing vitiligo were compared between a single dermascopic image (testing paper) and a combination of photographs, Wood's lamp examinations, and dermascopic images (training paper) by answering a questionnaire to eight dermatologists.ResultsWe have summarized the dermatoscopic features and clinical characteristics of 112 cases of active vitiligo, 111 cases of stable vitiligo, 99 cases of pityriasis alba, 94 cases of depigmented nevi, 16 cases of sclerosing atrophic moss, and 42 cases of post-inflammatory hypopigmentation in children. In this study, a statistically significant difference (p < 0.05) was found in the dermatoscopic characteristics between vitiligo at different stages and several other pigmentary disorders. Meanwhile, the trichrome pattern at the periphery of the lesion [area under the curve (AUC) = 0.8834, sensitivity 89.19%, specificity 87.5%] and the micro-Koebner/comet tail phenomenon (AUC = 0.7812, sensitivity 99.1%, specificity 57.14%) showed better diagnostic efficacy for active vitiligo, while the pigmentation at the periphery of the lesion (AUC = 0.8746, sensitivity 91.89%, specificity 83.04%) showed better diagnostic efficacy for stable vitiligo. The mean score (79.75 ± 10.45 vs. 71 ± 3.85; p = 0.058) and median time [555.50 (705) vs. 374 (1,011) s; p = 1,000] for physicians completing training and testing papers showed no statistical difference.ConclusionDermatoscopy can serve as a standalone tool for diagnosing vitiligo in children and may also help in staging the condition.